Pedagogical System for Preparation of Young People for Military Service - Tarakhanov Akrom Abdullahakimovich; Dadajonov Izzatulo Tavakkaljon oglu (Zien Journals, 2022)
The most important condition for the construction of a modern Armed Forces and their combat readiness is the effective and quality preparation of conscripts for military service. The issue of fulfilling the orders of the Armed Forces and the training of conscripts has always been in the center of attention of researchers, but it was not a priority. Its seriousness was offset by the size of the contingent, which allowed for the careful selection of candidates for military accounting specialties that required basic training, as well as sufficient time to train and educate servicemen from scratch
Keywords: ideology; education; youth; efficiency